Seleção recorrente intrapopulacional de meios-irmãos de milho visando o consumo fresco - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
In Brazil, corn is the second agricultural product with the highest production and harvested area, besides, it exerts socioeconomic importance, for being used in animal feed, in the form of dry grains and, human, mainly as green corn. However, the reduced number of green corn cultivars available for commercialization discourages producers from supplying this niche market. Consequently, lineages, hybrids and varieties are necessary to increase the profitability of producers and serve the various regions of cultivation. The objective of the study was to select families of half-brothers of corn, in five cycles of recurrent intrapopulation selection, aiming at in natura consumption, as well as to evaluate the possibility of obtaining a variety with desirable agronomic characteristics to, the productive chain of green corn. The experimental design used was that of randomized blocks, with 64 progeny of half brothers and three repetitions. The relative chlorophyll index (IRC), plant height (ALTP) and ear height (ALTE), diameter (DIAM) and ear length (COMP) were evaluated, as well as the productivity of stuffed ears (PEE) and commercial (PEC). The average gains obtained in each selective cycle, for the main characteristics of economic interest of green corn, the ear diameter, ear length, stuffed ear productivity and commercial ear productivity, indicated the possibility of success by continuing with intrapopular recurrent selection, with potential gains in other selective cycles and, in the future, obtaining a productive variety adapted to the soil and climate conditions of southeast Goiás.
Keywords: Zea mays L.; Melhoramento Vegetal; Milho Verde; Espigas Empalhadas; Espigas Comerciais; Zea mays L.; Productivity; Plant breeding; Vegetable Corn; Unhusked Ears; Commercial Ears; CIENCIAS AGRARIAS